Synthesis of YVO4 Ceramic Doped with Europium using Combustion Synthesis Method as a Down-Shifting Material for Solar Cell Applications - A. H. Nosohi; S. M. Rafiaei; M. Ebrahimi; A. Kermanpur (Journal of Advanced Materials in Engineering)
Recently, luminescent down-shifting materials, as promising materials, have attracted much interest to improve the performance of photovoltaic systems. Accordingly, the aim of this study was to synthesize the YVO4:Eu3+ powder by combustion method and characterize their photo luminescent properties as a layer deposited on silicon solar cell. The results of the study revealed that the YVO4:Eu3+ powder with an average particle size of about 80 nm was successfully synthesized. Fourier transform infrared spectroscopy (FTIR), ultraviolet-visible spectroscopy, and photoluminescence spectroscopy (PL) were used to investigate the properties of the synthesized powder, their deposition ability on the silicon solar cell, and their effects on the cell performance. The results indicated that the synthesized powder as a luminescent down-shifting material can absorb the ultraviolet light and convert it to visible light. The findings revealed that the deposition of YVO4:Eu3+ on the silicon solar cells can be considered as a promising and effective method to improve the performance of silicon solar cells in terms of power conversion efficiency and long term stability.